Four forage sorghum silage additives evaluated - Bolsen, K.K.; Riley, Jack G.; Hoover, J.D. (Kansas State University. Agricultural Experiment Station, 2011)
Two trials were conducted to evaluated four forage sorghum silage additives: ammonium iso-butyrate, aureomycin, sodium hydroxide, and a mixture of acetic and propionic acids. A control silage received no additives.
Keywords: Beef; Forage sorghum; Performance; Crude protein